The Effectiveness of Using Arabic Domino Cards to Improve Vocabulary Mastery : فعالية استخدام بطاقة الدومينو العربية لترقية سيطرة المفردات - Jannah, Miftahul; Mulya, Sri (Al Mihwar: Jurnal Pendidikan Bahasa Arab dan Kebahasaan, 2025)
This study investigates the problem of limited vocabulary mastery among students, which is often caused by teachers’ minimal use of engaging learning media. To address this challenge, the researcher implemented Arabic domino cards as a learning tool to improve students’ vocabulary acquisition. The research employed a pre-experimental design using a one-group pre-test post-test method, conducted with 17 fifth-grade students at Public Elementary School 23, North Aceh. Data were collected through pre-tests and post-tests and analyzed using the N-Gain Score and T-Test with SPSS 29. The results revealed that student activities while learning with Arabic domino cards reached a highly effective level, with an adjusted N-Gain Score of 78.34%. The T-Test analysis showed a significance value of 0.01 (p < 0.05), indicating a statistically significant improvement in students’ vocabulary mastery. Based on these findings, the study concludes that the use of Arabic domino cards is an effective instructional medium for enhancing vocabulary mastery among elementary school students.